EUROPEAN SECURITY POLICY AND THE ROLE OF INTERNATIONAL ORGANIZATIONS (COUNCIL OF EUROPE, OSCE, THE EU) IN THE CONFLICT SOLUTION IN EASTERN UKRAINE - Katsevych, Tetiana; Fedorchenko, Iryna (Київський національний університет імені Тараса Шевченка, 2020)
The situation in Ukraine concerns the international community since January 2014 and remains a central issue in legal and political science researches. The United Nations Security Council (UN) was not only unable to prevent the conflict but also to take any possible steps to resolve it. As a result, a number of regional European organizations have been involved in the crisis in eastern Ukraine. The article discusses the mechanisms of activity of key European structures and organizations which aim at preventing, mitigating and resolving the conflict in Ukraine. The specifics of the methods used by each organization are determined, the success of their activities is evaluated, and the ways of increasing their effectiveness and involvement in resolving the Russian-Ukrainian conflict are suggested. The international response of the European community to the conflict in Crimea and eastern Ukraine has been investigated. The approaches, activities and efforts of the OSCE, the EU and the Council of Europe to address the conflict are reviewed. As the crisis in Ukraine deepened, the tasks of the OSCE Monitoring Mission included the following: facilitating access of international experts to the MH17 crash place, monitoring the implementation of Minsk agreements, facilitating the dialogue on local level to achieve a temporary ceasefire, participating in humanitarian sector coordination groups, ongoing supplying with the information regional, national and international media on the current state of conflict. Accordingly, the situation should not be confined solely to the conflict between Ukraine and Russia, as it poses a threat not only to the territorial integrity of Ukraine but also to security in Europe, so the activities of international organizations should be assessed comprehensively with a focus on the need for international law to be respected by all parties concerned.

Ситуація в Україні викликає занепокоєння міжнародної спільноти, починаючи із січня 2014 року, і залишається центральною проблемою юридичних та політологічних досліджень. Рада Безпеки Організації Об’єднаних Націй (ООН) виявилася не в змозі не тільки попередити виникнення конфлікту, але й вжити будь-яких можливих заходів щодо його врегулювання. Як результат, низка регіональних європейських організацій виявилася втягнутою у кризу на сході України. У статті розглядаються механізми діяльності ключових європейських структур та організацій, спрямовані на запобігання, послаблення та врегулювання конфлікту в Україні. Визначено специфіку методів, що застосовуються кожною організацією, оцінюється успішність їх діяльності та пропонуються шляхи підвищення ефективності їх впливу та залученості у розв’язання російсько-українського конфлікту. Досліджено міжнародну реакцію європейської спільноти на конфлікт у Криму та на сході України; розглянуто підходи, діяльність та зусилля ОБСЄ, ЄС та Ради Європи щодо врегулювання конфлікту. По мірі поглиблення кризи в Україні, завдання Моніторингової місії ОБСЄ включали: полегшення доступу міжнародних експертів до місця аварії рейсу MH17, моніторинг виконання мінських домовленостей, сприяння діалогу на місцевому рівні для досягнення тимчасового перемир’я, участь у координаційних групах гуманітарного сектору, постійне інформування місцевих, регіональних, національних та міжнародних ЗМІ про поточний стан подій. Відповідно, ситуація не повинна зводитися виключно до конфлікту між Україною та Росією, оскільки становить загрозу не лише територіальній цілісності України, але й безпеці в Європі, тому діяльність міжнародних організацій слід оцінювати всебічно, з акцентом на необхідності дотримання міжнародного права всіма зацікавленими сторонами.
ЄВРОПЕЙСЬКА ПОЛІТИКА БЕЗПЕКИ ТА РОЛЬ МІЖНАРОДНИХ ОРГАНІЗАЦІЙ (РАДА ЄВРОПИ, ОБСЄ, ЄС) У ВИРІШЕННІ КОНФЛІКТУ НА СХОДІ УКРАЇНИ
Keywords: OSCE; collective security; aggression; Russian-Ukrainian war; European security policy; EU; Council of Europe; monitoring mission; колективна безпека; агресія; ОБСЄ; російсько-українська війна; політика європейської безпеки; ЄС; Рада Європи; моніторингова місія